Stellar Dynamics and the implications on the merger evolution in NGC6240 - Tecza, M; Genzel, R; Tacconi, L; Anders, S; Tacconi-Garman, L; Thatte, N (Institute of Physics Publishing, 2000)
We report near-infrared integral field spectroscopy of the luminous merging galaxy NGC 6240. Stellar velocities show that the two K-band peaks separated by 1.6arcsec are the central parts of inclined, rotating disk galaxies with equal mass bulges. The dynamical masses of the nuclei are much larger than the stellar mass derived from the K-band light, implying that the progenitor galaxies were galaxies with massive bulges. The K-band light is dominated by red supergiants formed in the two nuclei in starbursts, triggered ~2x10^7 years ago, possibly by the most recent perigalactic approach. Strong feedback effects of a superwind and supernovae are responsible for a short duration burst (~5x10^6 years) which is already decaying. The two galaxies form a prograde-retrograde rotating system and from the stellar velocity field it seems that one of the two interacting galaxies is subject to a prograde encounter. Between the stellar nuclei is a prominent peak of molecular gas (H_2, CO). The stellar velocity dispersion peaks there indicating that the gas has formed a local, self-gravitating concentration decoupled from the stellar gravitational potential. NGC 6240 has previously been reported to fit the paradigm of an elliptical galaxy formed through the merger of two galaxies. This was based on the near-infrared light distribution which follows a r^1/4-law. Our data cast strong doubt on this conclusion: the system is by far not relaxed, rotation plays an important role, as does self-gravitating gas, and the near-infrared light is dominated by young stars.